Demonstrating the reduction of enteric viruses by drinking water treatment during snowmelt episodes in urban areas. (1st May 2021) - Sylvestre, Émile; Prévost, Michèle; Burnet, Jean-Baptiste; Pang, Xiaoli; Qiu, Yuanyuan; Smeets, Patrick; Medema, Gertjan; Hachad, Mounia; Dorner, Sarah
Abstract: This study investigates short-term fluctuations in virus concentrations in source water and their removal by full-scale drinking water treatment processes under different source water conditions. Transient peaks in raw water faecal contamination were identified using in situ online β-d -glucuronidase activity monitoring at two urban drinking water treatment plants. During these peaks, sequential grab samples were collected at the source and throughout the treatment train to evaluate concentrations of rotavirus, adenovirus, norovirus, enterovirus, JC virus, reovirus, astrovirus and sapovirus by reverse transcription and real-time quantitative PCR. Virus infectivity was assessed through viral culture by measurement of cytopathic effect and integrated cell culture qPCR. Virus concentrations increased by approximately 0.5-log during two snowmelt/rainfall episodes and approximately 1.0-log following a planned wastewater discharge upstream of the drinking water intake and during a β-d -glucuronidase activity peak in dry weather conditions. Increases in the removal of adenovirus and rotavirus by coagulation/flocculation processes were observed during peak virus concentrations in source water, suggesting that these processes do not operate under steady-state conditions but dynamic conditions in response to source water conditions. Rotavirus and enterovirus detected in raw and treated water samples were predominantly negative in viral culture. At one site, infectious adenoviruses were detected in raw water and water treated by a combination of ballasted clarification, ozonation, GAC filtration, and UV disinfection operated at a dose of 40 mJ cm −2 . The proposed sampling strategy can inform the understanding of the dynamics associated with virus concentrations at drinking water treatment plants susceptible to de facto wastewater reuse. Graphical abstract: Image 1 Highlights: β-d -glucuronidase guided monitoring was used to investigate virus reduction. Raw water virus concentrations increased by 1.0-log during β-d -glucuronidase peaks. Virus removal during snowmelt events was similar or better than in baseline conditions. Infectious adenoviruses were detected after UV disinfection.